Las bases generales de los bienes municipales en el Derecho Administrativo Peruano - Vignolo Cueva, Orlando (Revista de Derecho, 2019)
The present publication seeks to develop and explain the different law sources applicable to Peruvian municipal property, considering its conceptual autonomy and specificity in relation to other public property and the system components diversity (including all sorts of legislative sources and territorial scope, constitutional case law and specially diverse municipal regulation). This publication intends to achieve a minimum systematic order, which helps to develop legal solutions on day-to day cases, considering the present is disordered and difficult law specialty.